Lab-scale anaerobic digestion of cassava peels: the first step of energy recovery from cassava waste and water hyacinth. Issue 9 (16th April 2021) - Ahou, Yaovi Sylvestre; Bautista Angeli, Jean-Romain; Awad, Sary; Baba-Moussa, Lamine; Andres, Yves
ABSTRACT: Cassava processing in Republic of Benin, which is used to produce different food products, discharges a large amount of polluting organic matter into the environment in the form of peels and wastewater. Besides, water hyacinth a rich nitrogen plant invades Benin water streams leading in aquatic ecosystem asphyxia and blocks the navigation. Both cassava wastes and water hyacinth show a high biodegradable content enable to be treated through anaerobic digestion. According to the literature, the main challenge in cassava wastes anaerobic digestion is early inhibition caused by a rapid acidification linked to low nitrogen and high biodegradable sugars content. This paper focused on the theoretical and biochemical methanogenic potential determination which is an essential step of recovery energy on large scale of both substrates. Stoichiometric methanogenic potentials of cassava wastes are close to the biochemical methanogenic potentials. However, it was necessary to treat cassava peels with potash « akanwu » and phosphate buffer pH 7.2. Average cumulative methane yield was 368 mL/gVS; 309 mL/gVS and 178 mL/gVS respectively for cassava wastewater (CWW), cassava peels (CP), water hyacinth (WH). Co-digestion of cassava peels with water hyacinth yielded on average 211 mLCH4/gVS. Despite that methane yield of co-digestion was lower than the summative methane yield of each substrate, the process has removed the chemicals products then improved cassava peels treatment. In addition, methane yield of water hyacinth increased by 10% when co-digested with cassava peels. GRAPHICAL ABSTRACT: